Refractory Chronic Pain Screening Tool (RCPST): A Feasibility Study to Assess Practicality and Validity of Identifying Potential Neurostimulation Candidates. Issue 2 (8th November 2013) - Baron, Ralf; Backonja, Misha M.; Eldridge, Paul; Levy, Robert; Vissers, Kris; Attal, Nadine; Buchser, Eric; Cruccu, Giorgio; De Andrés, Jose; Hansson, Per; Jacobs, Marilyn; Loeser, John D.; et al.
Abstract Objective An international panel of pain specialists (anesthesiology, neurology, neurosurgery, and psychology) and research methodologists developed a screening tool to identify patients who may be suitable for spinal cord stimulation (SCS)—the Refractory Chronic Pain Screening Tool (RCPST) prototype. We describe a feasibility study to explore practicality and validity of this prototype. Design Consecutive outpatients were screened in two centers (United Kingdom and United States). Sixty chronic pain adults without satisfactory pain relief despite treatment were assessed using RCPST (by pain specialist without expertise in neurostimulation) and then evaluated by two pain specialists experienced in SCS implantation and management to determine whether the patient should be referred for SCS. To maintain blinding, the participating physicians did not inform each other or the patient of assessment outcome. Sensitivity and specificity of the RCPST prototype were calculated using implanters' judgment as "gold standard." Results The average age of patients was 47.7 years; 53% were female. Fifty‐seven patients completed the study (one withdrew consent, two lost to follow‐up). The pain specialists agreed the prototype was easy to use and took <10 minutes to complete. Implanter agreement was moderate (Kappa: 0.63, 95% confidence interval: 0.35–0.91). The prototype had low sensitivity (40%, 19–61%) and moderate specificity (78%, 65–92%). Using the same questionnaire with a modified decision algorithm, new prototypes were generated with range of high sensitivity (80–100%) and specificity (89–97%) values. Conclusions The RCPST aims to identify patients that should be referred for consideration for neurostimulation. The final implant decision requires appropriate neurological diagnostic workup, psychological assessment, and trial stimulation. RCPST was considered practical for routine clinical practice and contained appropriate questions. Sensitivity needs to be improved. A future study should select and validate the ideal RCPST prototype.